Management of Airway Foreign Body Aspiration with Atelectasis Complication - Puji Utami; Rizka Fathoni Perdana (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: A sharp foreign body aspirationis a problem that is usually found in teenage women who wear hijab.Straight-pins are used in wearing hijab to make a model and to hold it tight in place. Straight-pin aspiration has thepotential to become a serious problem if it is inhaled in the airway and must be removed immediately in optimalconditions by using complete equipment to prevent complications.Case Report: A 14 year old girl with straight-pin aspiration in the airwayhad come to emergency room ofDrSoetomo General AcademicHospital, Surabaya, Indonesia. The initial location of the straight-pinwas in the rightmain bronchus and a rigid bronchoscopy was planned. Rigid bronchoscopy was performed but the foreign objectfailed to be removed and the foreign object moved further down and difficult to reach. A flexible bronchoscopywas performed and the foreign body was successfully removed. However, there was a complication of left lungatelectasis after the procedure. It was treated conservatively and healed.Conclusion: Straight-pin aspirationin the airway is treated by rigid and flexible bronchoscopy with atelectasis asa complication. Flexible bronchoscopy is an alternative therapy for inhaled foreign bodies that are located distallyand cannot be reached by rigid instruments.